Uniaxially stretched polyethylene/boron nitride nanocomposite films with metal-like thermal conductivity. (18th August 2020) - Zhang, Ri-Chao; Huang, Zirui; Huang, Zhihuan; Zhong, Meiling; Zang, Dongmian; Lu, Ai; Lin, Yuanfei; Millar, Bronagh; Garet, Graham; Turner, Josh; Menary, Gary; Ji, Dehui; et al.
Abstract: Achieving ultra-high thermal conductivity while maintaining the electrical insulation of polymers is highly desirable for many applications such as thermal management and packaging. In this work, polyethylene/boron nitride nanoplatelets (PE/BNNP) nanocomposite film was produced through melt processing followed by uniaxial stretching. Microstructural analysis reveals that the stretched composite film features a co-continuous network structure which consists of oriented lamellae bridged by both stretched polymer chains and aligned BNNPs along the stretching direction. The resulting film exhibit a metal-like thermal conductivity as high as 106 W m −1 K −1 and it is believed that the unique network structure has enabled efficient phonon transfer across the film, resulting in superior thermal transporting performance. This work shines a light on the design and scalable manufacturing of high performance functional polymer-based composites for future thermal management applications.